2018
DOI: 10.1002/jcp.27636
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of three strategies for biopanning of phage‐scFv library against diphtheria toxin

Abstract: The biopanning process is a critical step in phage display for isolating peptides or proteins with specific binding properties. Conventional panning methods are sometimes not so effective and may result in nonspecific or low‐yield positive results. In this study, three different strategies including soluble antibody‐capturing, pH‐stepwise elution, and conventional panning were used for enrichment of specific clones against diphtheria toxoid. The reactivity of the selected clones was evaluated using an indirect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Selection of antibodies against human PCSK9. The recombinant human scFv phage library was screened against PcSK9 as previously reported (13,14). Immunotubes were coated with detection antigen (purified PCSK9) diluted to 100 µg/ml (2 ml/immunotube) and incubated at 4˚C overnight.…”
Section: Construction Of a Fully Human Scfv Phage Display Antibody LImentioning
confidence: 99%
“…Selection of antibodies against human PCSK9. The recombinant human scFv phage library was screened against PcSK9 as previously reported (13,14). Immunotubes were coated with detection antigen (purified PCSK9) diluted to 100 µg/ml (2 ml/immunotube) and incubated at 4˚C overnight.…”
Section: Construction Of a Fully Human Scfv Phage Display Antibody LImentioning
confidence: 99%
“…In a recent example, four different biopanning strategies, including the immobilization of recombinant protein to polystyrene beads and different cell-based methods, evaluated the selection output when incorporating various depletion and blocking steps [ 38 ]. Lakzaei and colleagues compared the effects of an antigen in solution to the same antigen immobilized on a carrier surface and found that the soluble approach was more efficient for isolating functional antibody fragments against the target [ 39 ]. However, comparative studies reported in the literature mainly focus on the optimization of strategies, including pH-elution parameters [ 39 , 40 ], the impact of depletion and negative selection [ 41 ], and the use of different antigen capture reagents [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lakzaei and colleagues compared the effects of an antigen in solution to the same antigen immobilized on a carrier surface and found that the soluble approach was more efficient for isolating functional antibody fragments against the target [ 39 ]. However, comparative studies reported in the literature mainly focus on the optimization of strategies, including pH-elution parameters [ 39 , 40 ], the impact of depletion and negative selection [ 41 ], and the use of different antigen capture reagents [ 42 , 43 , 44 ]. Here, we show that biopanning strategies employing the surface-tethered recombinant ECD of an integral type I membrane protein were more effective in isolating a functional binder compared to biopanning with the full-length protein in the cellular membrane environment.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we compared three different panning procedures: panning in MTP with directly immobilized antigen, panning in solution with biotinylated antigen and capture panning with human Fc-tagged antigen. Compared to the panning in MTP the panning in solution is slightly more complex but allows the target to be present in its native form which can lead to improved epitope accessibility [26,32]. The protocol with captured antigen is comparable to the protocol with directly immobilized antigen but potentially allows better target accessibility.…”
Section: Discussionmentioning
confidence: 99%